Uncovering Student Ideas in Science: 25 Formative Assessment Probes Vol.3 - Page Keeley, Francis Eberle and Lynn Farrin (National Science Teachers Association, 2017)
This third volume in our best-selling series Uncovering Student Ideas in Sciencecontains 25 all new "probes" to uncover students' misconceptions in science and offers guidance on how teachers can use the probes for their own learning. Since publication of volume 1 of the series, thousands of teachers have been using these innovative classroom tools to improve student learning in science. Following in the footsteps of the blockbusters Volumes 1 and 2, this book provides short, easy-to-administer probes that determine what scientific misunderstandings your students may bring into your classroom without your even knowing it! Volume 3 offers five life science probes, seven Earth and space science probes, ten physical science probes, and three nature of science probes. This volume is an invaluable resource for classroom teachers, preservice teachers, professional developers, and college science and preservice faculty.